2017
DOI: 10.14260/jemds/2017/1136
|View full text |Cite
|
Sign up to set email alerts
|

Timeliness of Childhood Vaccine Uptake Among Children Attending Immunoprophylaxis Clinic in Central India

Abstract: BACKGROUNDChild survival is dependent on many survival factors including immunisation. Even though, vaccines are provided free of cost at all government healthcare centers, the immunisation coverage in India is very low. Delayed vaccination not only increases the risk of vaccine preventable disease, but also increases the risk of never fully completing the vaccination course. The present study assessed the timeliness of immunisation for children below one year of age and factors influencing the timeliness of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…In the previous studies so far, factors such as home delivery ( 19 ), low-education attainment and below four antenatal care visits ( 20 ), unplanned pregnancy and child male sex ( 21 ), highest mothers/caregivers age ( 22 ), vaccine hesitancy ( 5 ), being a multiparous mother ( 23 ), and rural children and poorest quintile ( 17 ) were independently associated with the vaccine timeliness. However, these factors are different depending on the study context ( 24 ).…”
Section: Introductionmentioning
confidence: 95%
“…In the previous studies so far, factors such as home delivery ( 19 ), low-education attainment and below four antenatal care visits ( 20 ), unplanned pregnancy and child male sex ( 21 ), highest mothers/caregivers age ( 22 ), vaccine hesitancy ( 5 ), being a multiparous mother ( 23 ), and rural children and poorest quintile ( 17 ) were independently associated with the vaccine timeliness. However, these factors are different depending on the study context ( 24 ).…”
Section: Introductionmentioning
confidence: 95%
“…In sub-Saharan African countries, including Ethiopia, vaccination delays have been a bottleneck issue [ 9 ]. Even though factors of vaccine timeliness vary with the study context [ 10 ], pieces of evidence from the previous study revealed that the risk factors of vaccine timeliness are home delivery [ 11 ], low-education attainment and below four antenatal care visits [ 12 ], unplanned pregnancy and child male sex [ 13 ], highest mothers/caregivers age [ 14 ], vaccine hesitancy [ 15 ], being a multiparous mother [ 16 ], and rural children and poorest quintile [ 8 ]. Like other countries, in Ethiopia, age-appropriate vaccination is the key strategic activity to reduce easily preventable childhood mortality from measles, pneumonia, diarrheal diseases, and other vaccine preventable diseases [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among these challenges, the problem of supply chain management, health services, and the performance of the health care provider is the most common factor [10]. Even though the factors of timely vaccination are very contextual [11], home delivery [12], low-education attainment and below four antenatal care visits [13], unplanned pregnancy and child male sex [3], highest mothers/caregivers age [14], vaccine hesitancy [15], being a multiparous mother [16], and rural children and poorest quintile are also affected the timely vaccination [10].…”
Section: Introductionmentioning
confidence: 99%